Modeling the impact of sea level rise in the Guadiana estuary - Mills, Lara Kaitlyn (2021)
Sea level rise is a global concern as a large percentage of the population live on the coast. The focus of this study is the impact of sea level rise on the Guadiana Estuary, an estuary in the Iberian Peninsula formed at the interface of the Guadiana River and the Gulf of Cadiz. Estuaries will be largely affected by sea level rise as these transitional environments host highly diverse and complex marine ecosystems. Model-based projections of sea level rise demonstrate that global mean sea level rise is accelerating. Major consequences of sea level rise are the intrusion of salt from the sea into fresh water as well as an increase in flooding area. Not yet fully explored in the literature are the effects of sea level rise on salinity concentrations in estuarine environments. As the physical, chemical and biological components of estuaries are sensitive to changes in salinity, the purpose of this study is to further evaluate salt intrusion and flooding in the Guadiana Estuary caused by sea level rise and the socioeconomic effects of areas surrounding the estuary. Hydrodynamics of the Guadiana Estuary were simulated in a two-dimensional numerical model with the MOHID water modeling system. A previously developed hydrodynamic model was used to further examine evolution of salinity transport in the estuary as well as flooding areas in response to sea level rise. Varying tidal amplitudes, freshwater discharge from the Guadiana River and bathymetries of the estuary were incorporated in the model to fully evaluate the impacts of sea level rise on salinity transport and flooding areas of the estuary. Results show an overall increase in salinity and land inundation in the estuary in response to sea level rise. The salinity extends westward and eastward to the saltmarshes of the estuary when there is a high freshwater discharge from the Guadiana River. Salinity extends further up the main channel when the freshwater discharge is low.